Synthesis of Zinc Oxide Nanoparticles Using Leaf Extract of Lippia adoensis (Koseret) and Evaluation of Its Antibacterial Activity - Meron Girma Demissie; Fedlu Kedir Sabir; Gemechu Deressa Edossa; Bedasa Abdisa Gonfa (Journal of Chemistry)
The synthesis of metal oxide nanoparticles with the use of medicinal plant extract is a promising alternative to the conventional chemical method. This work aimed to synthesize zinc oxide nanoparticles using a green approach from indigenous “Koseret” Lippia adoensis leaf extract which is an endemic medicinal plant and cultivated in home gardens of different regions of Ethiopia. The biosynthesized zinc oxide nanoparticles were characterized using thermogravimetric analysis, X-ray diffraction, scanning electron microscopy-energy dispersive spectroscopy, transmission electron microscopy, ultraviolet-visible spectroscopy, and Fourier transform infrared spectroscopy. Furthermore, this study also evaluated the antibacterial activity of the synthesized ZnO nanoparticles against clinical and standard strains of Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus, and Enterococcus faecalis by the disc diffusion method. According to the result of this study, ZnO nanoparticles synthesized using Lippia adoensis leaf extract showed promising result against both Gram-positive and Gram-negative bacterial strains with a maximum inhibition zone of 14 mm and 12 mm, respectively, using uncalcinated form of the synthesized ZnO nanoparticles.